A phase 2, multicenter study investigating ofatumumab and bendamustine combination in patients with untreated or relapsed CLL. Issue 9 (3rd July 2016) - Flinn, Ian W.; Panayiotidis, Panayiotis; Afanasyev, Boris; Janssens, Ann; Grosicki, Sebastian; Homenda, Wojciech; Smolej, Lukas; Kuliczkowski, Kazimierz; Doubek, Michael; Domnikova, Natalia; West, Sarah L.; Chang, Chai‐Ni; et al.
Abstract : The purpose of this study is to assess the safety and efficacy of the combination of ofatumumab and bendamustine in patients with previously untreated or relapsed chronic lymphocytic leukemia. Patients received IV ofatumumab (cycle 1: 300 mg day 1 and 1, 000 mg day 8; cycles 2–6: 1, 000 mg on day 1 every 28 days) and IV bendamustine 90 mg m −2 (previously untreated) or 70 mg m −2 (relapsed) on days 1 and 2 of each 28‐day cycle, for up to 6 cycles. Forty‐four previously untreated and 53 relapsed patients were enrolled. Median age was 62.5 years (previously untreated) and 68 years (relapsed); relapsed patients had received a median of 1 (range 1–11) prior therapy. The investigator‐assessed overall response rate was 95% (43% complete response [CR]) for the previously untreated, and 74% (11% CR) for the relapsed patients. The regimen was well tolerated with 89% (previously untreated) and 85% (relapsed patients) receiving all 6 cycles. No unexpected toxicities were reported. Grade 3/4 events occurred in 57% of previously untreated, and 72% of relapsed patients. At ∼29 months' follow‐up, the median progression‐free survival (PFS) was not reached for the previously untreated population, and the 28‐month PFS estimate was 72.3%. The median PFS for the relapsed population was 22.5 months (95% CI: 14.0–27.3 months). The combination of ofatumumab and bendamustine was well tolerated and effective in these previously untreated or relapsed populations. Am. J. Hematol. 91:900–906, 2016. © 2016 Wiley Periodicals, Inc.